ANALISIS PEMASARAN HASIL PERIKANAN LAUT IKAN LAYANG (Decapterus russelli) DAN IKAN TONGKOL (Euthynus sp) DI PANGKALAN PENDARATAN IKAN (PPI) SELILI KOTA SAMARINDA - Wulandari; Juliani; Fitriyana (Jurnal Pembangunan Perikanan dan Agribisnis, 2014)
This research aims to know about marketing channel and function of marketing is measure by margin, eficiency and marketing benefit of the catch marine fisheries. Average revenue of wholesaler is Rp 30.000.000,00 by the trip, average revenue of agent is Rp 24.561.111,00 by the month and average revenue of retailer is Rp 9.998.900,00 by the month. Average benefit of wholesaler is Rp 17.843.431,00 by the trip, average income of agent is Rp 13.051.319,00 by the month and average income retailer is Rp 5.565.650,00 by the month. Total margin is Rp 16.865,00 and Marketing Efficiency is 56 % for Scads (Decapterus russelli) and 59 % for Eastern Little Tunas (Euthynus sp).